Impact of Digital Rituals on Modern Tribal Societies: A Comparative Study - Anholt Trudy; Rongzhen Julie; Vigne Pierre (Yayasan Adra Karima Hubbi, 2024)
Digital transformation has changed various aspects of people's lives, including ritual practices and modern tribal culture. Digital rituals, combining technology with tradition, are becoming increasingly common among modern tribal societies. These changes raise questions about the impact of digital technologies on the sustainability of cultural traditions and tribal identity. This study aims to analyze the impact of digital rituals on modern tribal societies. The study compares tribes that have adopted digital technology in their ritual practices and tribes that still maintain traditional practices. This research uses a qualitative and comparative case study method. Data were collected through in-depth interviews and participatory observations in two different modern tribal communities. Data analysis is performed using thematic analysis techniques to identify critical patterns and themes emerging from the data. The results showed that tribes that adopted digital rituals experienced significant changes in their cultural and social practices. Digital technologies facilitate the dissemination and preservation of rituals but also pose challenges in preserving the authenticity and meaning of traditions. Tribes that maintain traditional practices tend to be more vital in maintaining their cultural identity despite facing difficulties in the accessibility and participation of younger generations. The study concludes that digital rituals have a dual impact on modern tribal societies. While digital technologies can help preserve and spread cultural rituals, there is a risk of losing the authenticity and meaning of traditions. A balanced approach is needed to integrate digital technology into tribal cultural practices to maintain cultural identity while leveraging technological advantages.